Pengaruh Modelchildren’s Learning in Science untuk Meningkatkan Hasil Belajar Siswa Kelas V SD IMPRES 45 Wayame - Marayate, Glorya; Pelamonia, Johannes; Rumahlatu, Dominggus (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2026)
This study aims to examine the effect of the Children Learning in Science (CLIS) learning model on improving science learning outcomes of fifth-grade students at SD Impres 45 Wayame. The research employed a quantitative descriptive approach with 25 students as research subjects. The research instruments consisted of pretest and posttest to measure cognitive achievement, as well as observation sheets to assess affective and psychomotor aspects. The results showed that prior to the implementation of the CLIS model, all students (100%) had not achieved the Minimum Mastery Criteria (MMC). After the application of the CLIS model, students’ learning outcomes improved significantly across cognitive, affective, and psychomotor domains. The average posttest score reached 86.3, and all students achieved mastery learning. In addition, students’ affective and psychomotor skills were categorized as good to very good. Therefore, it can be concluded that the Children Learning in Science learning model is effective in improving science learning outcomes of fifth-grade elementary school students.